Communication and successful aging: Testing alternative conceptualizations of uncertainty. Issue 2 (3rd April 2019) - Gasiorek, Jessica; Fowler, Craig; Giles, Howard
ABSTRACT: The communicative ecology model of successful aging ( CEMSA ), which theorizes how people's communication can influence their experiences of successful aging, takes as axiomatic that aging involves uncertainty. In two studies, with data from the U.S. and the U.K., we compared the viability of two conceptualizations of uncertainty about aging in the CEMSA: the model's original operationalization, uncertainty discrepancy, and an alternative, the perceived probability of negative experiences (PPNE) associated with aging. In both studies, uncertainty discrepancy and PPNE contributed independently to attitudes toward aging; PPNE emerged as a stronger predictor of people's affective reactions to aging. These findings underscore the importance of multifaceted views of uncertainty for scholars of communication and aging.